Kebijakan Kepariwisataan di Provinsi Aceh: Peluang dan Tantangan - Herizal Herizal; Saddam Rassanjani; Muhkrijal Muhkrijal (Universitas Teuku Umar, 2021)
Tourism is a public sector that should be managed seriously to improve the livelihoods of many people. The potential of Aceh's tourism must be encouraged by quality public policies so that all of its potential will be maximized. In fact, there are still many weaknesses in public policies in the tourism sector that have rendered Aceh's tourism potential in vain. This study aims to describe Aceh's public policy in the tourism sector in terms of opportunities and challenges. The research approach used is a qualitative analysis through a literature review that relies on secondary data, namely by collecting and mapping data from government documents in the form of tourism plans, tourism regulations, work reports on tourism and similar studies on tourism policies. The results of the study show that the Aceh Government has seen great opportunities in the tourism sector, especially from halal tourism, but what remains a challenge until now is that the Government of Aceh has not resolved problems related to tourism governance, tourism destination development and tourism branding.